EXPERIMENTAL FIELD CULTURE OF WHITE PRAWN, PENAEUS INDICUS, IN THE POLYETHYLENE FILM - LINED PONDS USING PELLETISED FEED - Lazarus, S; Muthu, M S; Nandakumaran, K; Ali, S A (Indian Journal of Fisheries, 2011)
The results of two experiments on the culture of Penaeus indicus conducted during the year 1982 are given. A high survival rate of 99.2% was obtained for the prawns which were stocked at a mean size of 15.8mm. Maximum production rates obtained per hectare within a period of 83 days mono-culture under stocking densities 4, 5, 7 and 10/m2 were respectively 355, 253, 431 and 398 kg. The size of prawns at harvest ranged from 90.8 to 119.3 mm mean length and from 4.4 to 12.3 g mean weight. The instantaneous growth rate varied from 0.0211 to 0.0251 for length and from 0.0591 to 0.0720 for weight in the different ponds. The pelletised feed used in these experiments gave a good feed conversion ratio of 2.62 in one of the ponds.